Strategi Peningkatan Usaha Kecil Mikro dan Menengah (UMKM) di Era Pandemi Covid-19 Pada Kota Metro - Sigit Setioko; Yuyun Fitriani; Kholifatul Munawaroh (Indonesian Journal Publisher, 2022)
This paper outlines the formulation of strategies for small, Usaha kecil mikro dan menengah (UMKM) in the era of the Covid-19 pandemic in Metro City, where very tight business competition and declining public income as a result of the Covid-19 pandemic forced entrepreneurs to apply the best strategic management to deal with current economic downturn. The target of the service activity is MSME Metro actors who are affected by the COVID-19 pandemic, then UMKM actors are asked to fill out pre-test and post-test, then the data is processed, so as to produce data in the form of a description of the explanation of internal environmental studies in increasing the capacity of Metro City UMKM actors in improving business opportunities during the pandemic. The author describes the analysis of strategies that can be divided into 2, namely the analysis of internal factors and analysis of external factors. Internal factor analysis will discuss further the strengths and weaknesses of the business and external factor analysis will discuss opportunities and threats that can occur in the company. Internal and external factors of strategic management are usually acronymized as SWOT (Strength, Weakness, Opportunity, Threath). to support efforts to increase income during the pandemic through internal environmental scanning efforts. Although this commitment is informal and has not yet formed a Memorandum of Understanding (MoU).